Synthesis of Matrix Si-K-HAs Gel from Geothermal Sludge and Peat - Srie Muljani; Bambang Wahyudi Wahyudi; S Suprihatin; Ketut Sumada (Reaktor, 2018)
The synthesis of matrix silica-potassium-humic acid gel (Si-K-HAs) has been performed successfully by gradual extraction and acidification method. The extraction was carried out in two stages: 1) extraction of humic substances from peat prepared by potassium hydroxide to produce potassium humate (K-HAS) solution, 2) extraction silica from geothermal sludge using K-HAs solution to produce Si-K-HAs solution. Acidification of Si-K-HAs solution prepared by citric acid (1-3N) to produce matrix gel of Si-K-HAs. The Si-K-HAs matrix gel products are characterized by Fourier Transform InfraRed (FTIR), X-ray fluroscence (XRF), and Brunauer–Emmett–Teller (BET) analysis. The acidification process was carried out in neutral to acid (pH 3-7) conditions and the results showed that at neutral pH no Si-K-HAs gel formed. IR spectra confirmed the presence of humic acid in the gel product, whereas XRF analysis confirmed the presence of potassium (K) and silica (SiO2) in the gel product. The molar ratio of SiO2:K2O in the product is 0.9 - 0.3 in the pH range of 3-5. Si-K-HAs powder can be used as soil fertilizer especially for soils that lack silica, humic, and potassium nutrients or for future application development. Keywords: gradual extraction; geothermal sludge; matrix gel; humic substance